Discussion about Belarussian Church autocephaly during Nazi occupation of Belarus - I. V. Petrov (Омский научный вестник: Серия "Общество. История. Современность")
In 2020 in Belarus there was an intensification of the activities of forces sympathetic to the idea of separating the Orthodox on the territory of the Republic from the Russian Orthodox Church. This kind of reaction is not new to the republic. The idea of church autocephaly was most acutely discussed during the Nazi occupation of the BSSR. A book by the Belarusian church historian Andrey Pukanov is devoted to this period of history. The basis of the book is the materials of the Belarusian press. Memories of the participants, the legacy of the Belarusian post-war emigration. The article presents a critical analysis of the book of a modern Belarusian author